Notes from a totally lame vampire : because the undead have feelings too! - Collins, Tim, 1975- (Aladdin, 2010)
Nigel Mullet, a 100-year-old vampire doomed to spend eternity in the body of a socially awkward fifteen-year-old boy, records his attempts to impress the love of his life, Chloe, while battling an embarrassingly overwhelming desire to sink his fangs into her.